'BDS – it's complicated': Israeli, Jewish, and others' views on the boycott of Israel. Issue 7 (2nd September 2017) - Chaitin, Julia; Steinberg, Shoshana; Steinberg, Sharon
ABSTRACT: This study explored attitudes of 501 Israelis – Jews and non-Jews – and Jews and others from western countries concerning Boycott, Divestment and Sanctions (BDS) and the Palestinian Academic and Cultural Boycott of Israel (PACBI), which aim to change Israeli policy towards the Palestinians. We studied the relationships between views on BDS/PACBI, understandings of the Israeli-Palestinian conflict, and anti-Semitism, in the different groups. Our internet questionnaire led to snowball sampling, resulting in a highly-educated sample. Israeli-Jews were more inclined to participate than others. Few Palestinians from the Occupied Territories responded; hence we could not compare this group to the others. Overall, more respondents opposed the boycott than those who favoured it. Jewish-Israelis showed the lowest agreement with BDS while non-Jews from western countries exhibited the highest. Jewish-Israeli responses were similar to responses from western Jews and non-Jewish Israelis tended to respond like western non-Jews. Jewish respondents saw BDS as less non-violent than the other groups, while non-Jews disagreed more with the statement that BDS is anti-Semitic than the Jewish respondents. In conclusion, since views towards the boycott were found to be nuanced, researchers and activists need to be aware of these complexities when engaging in human rights work in the Israeli-Palestinian context.